KEPENTINGAN INDONESIA MEMPERBARUI KERJA SAMA PERJANJIAN PENGHINDARAN PAJAK BERGANDA (P3B) ATAU TAX TRETY DENGAN SINGAPURA TAHUN 2020 - Ismy Fenti Ismail; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Double taxation (P3B) or Tax Treaty is a feature in a country that plays a role in bridging the taxation interests of each country that makes an agreement. The existence of this P3B or Tax Treaty is to regulate the imposition of taxes that have international relations from the two countries that make the agreement so that there is no double taxation. This Tax Treaty plays an important role because the tax burden imposed by people or businesses who have relations with the two countries will affect investment and capital decisions between the two countries This study aims to examine Indonesia's Interests in Renewing the Double Taxation Avoidance Agreement (P3B) or Tax Treaty with Singapore in 2020. The author uses the perspective of liberalism and international cooperation theory in examining this issue. This type of research is qualitative with descriptive data processing. Data collection as a reference in this study was carried out using the library method, namely utilizing secondary data obtained from various literatures such as books, journals, annual reports of several related agencies, official documents, and so on. The results of this study found that the renewal of the P3B or Tax Treaty was to achieve Indonesia's interests, one of which was to attract many Singaporean investors to invest in Indonesia. The results of the amendments to the renegotiations carried out by Indonesia and Singapore are also updated in accordance with the international tax landscape and adapted to International Economic Developments. Keywords: P3B, Amendment, Renegotiation.